2016
DOI: 10.1140/epja/i2016-16020-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the basic parameters of neutron stars using model atmospheres

Abstract: Abstract. Model spectra of neutron star atmospheres are nowadays widely used to fit the observed thermal X-ray spectra of neutron stars. This fitting is the key element in the method of the neutron star radius determination. Here, we present the basic assumptions used for the neutron star atmosphere modeling as well as the main qualitative features of the stellar atmospheres leading to the deviations of the emergent model spectrum from blackbody. We describe the properties of two of our model atmosphere grids:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 77 publications
3
35
0
Order By: Relevance
“…The radius of the 1.4M NS is about 12 km, agreeing with the analysis of NS data in [67] and with a recent analysis using the cooling tail method [68], see also Ref. [9] and the contribution to this volume [69].…”
Section: Equation Of Statesupporting
confidence: 90%
See 1 more Smart Citation
“…The radius of the 1.4M NS is about 12 km, agreeing with the analysis of NS data in [67] and with a recent analysis using the cooling tail method [68], see also Ref. [9] and the contribution to this volume [69].…”
Section: Equation Of Statesupporting
confidence: 90%
“…The DD2vex family of EoS [71] has been used as a basis for a Bayesian M-R analysis in order to extract the most probable EoS behaviour at high densities [80], Applying the constraint for the nearest millisecond pulsar PSR J0437-4715 [53,70] which yields rather large radii ∼ 15 km, in this analysis the stiffest possible hadronic EoS supporting NS with large radii get selected as the most probable ones. This large radius constraint has a preference over other results for the radii since its analysis is not flawed by the uncertainties due to unknown atmospheric composition [81] or controversial interpretation of data from X-ray bursters, see the corresponding contributions to this volume [69,82]. One of those stiffest possible EoS is DD2vex, which we will exploit in the given work, with a van-der-Waals excluded volume parameter v = 16πr 3 N /3 = 4.0 fm 3 that corresponds to a nucleon radius of r N 0.6 fm.…”
Section: Equation Of Statementioning
confidence: 99%
“…For SU(3) NJL, the smallest radius obtained is 13.35 km above the 10.1-11.1 km prediction of [49] from the analysis of spectroscopic radius measurements during thermonuclear bursts or in quiescence or even the 12.1 AE 1.1 km obtained in [50] from experimental constraints and causality restrictions. However, in [51] radii above 13 km were obtained for X-ray bursting NS and in [52] it has been shown that causality together with the 2 M ⊙ constraints imposes R > 10.7 km. For a recent review of the current status of measurements of radius of neutron stars see [53].…”
Section: B the Role Of Strangenessmentioning
confidence: 99%
“…1 in Kajava et al 2014 andSuleimanov et al 2016 for the interpretation). It should also be kept in mind that Fe emission features are caused by gas that is only partly ionized; it is possible that the accretion flow extends further in, where Fe is fully Fig.…”
Section: Additional Notes On Reflection and Spectral Featuresmentioning
confidence: 99%